The Impact of Sustainable Innovation on Environment, Social and Governance (ESG) Framework: A Moderating Paradigm from Research and Development (R&D) Expenses - Akter, Shahnaz; Hoque, Emranul (Business Management and Strategy, 2024)
In recent years, businesses are giving more and more emphasis to create sustainable innovations that balance economic, environmental, and social objectives. The objective of this paper is to investigate the impacts of sustainable innovation on Environmental, social and governance (ESG) performance. This paper also examines the moderating effect of Research and Development (R&D) expenses on sustainable innovation and ESG. The analysis makes use of information from 34 Bangladeshi listed firms from 2018 to 2022. A content analysis method was applied to collect the panel data from secondary sources. To test the study hypotheses, multiple regression analysis is employed. The result shows that sustainable innovation has a positive impact on ESG performance. In addition, the study also found that R&D has no significant effect on the relationship between sustainable innovation and ESG performance. The results could assist managers and policymakers in developing nations in establishing sustainable innovation strategies to attain ESG performance. This is the yardstick study towards SDGSs to examine the impacts of Sustainable innovation and ESG performance considering R&D expenses as a moderating variable in the context of Bangladesh, an emerging country.